Sweet potato (Ipomoea botatus L.) as a component of swine ration - YADAV, B P S; GUPTA, H K; GUPTA, J J (The Indian Journal of Animal Sciences, 2013)
Two experiments were conducted for the nutritional evaluation of sweet potato (Ipomoea botatus L.) in swine ration. In experiment 1, crossbred male pigs (12), 7 months old, were randomly allotted to 3 treatments and were kept on feeding schedule comprising control ration with conventional concentrate (T1); ad lib. feeding of sweet potato tubers with vines as basal feed supplemented with 50% Concentrate of control (T2) and only sweet potato tubers with vines ad lib. (T3). The DM intake (kg/100 kg b wt) was 3.72±0.21, 4.52±0.26 and 2.73±0.09 with digestibility of DM as 64.93±2.01, 77.54±1.46 and 85.08±1.92% in T1, T2 and T3 respectively. In experiment 2 crossbred male pigs (8) of similar age were randomly assigned 102 treatments comprising conventional concentrate with maize (A) and replaccmem of maize(40%) with sweet potato tubers (B). The DM intake and growth were similar in both the treatments. Digestibilities of nutrients were higher in rations based on sweet potato tuber. Rations based on sweet potato were highly palatable and digestible. The growth was, however, lower than conventional concentrate feed. An adequate supplementation of protein was necessary.